Asymptomatic Bacteriuria in pregnant women attending a tertiary hospital in northern India: prevalence, risk factors, causative organisms and antimicrobial sensitivity pattern - Multani, Harman; Bashir, Humaira; Aleem, Seema (Asian Journal of Medical Sciences, 2021)
Background: Asymptomatic bacteriuria is common and can lead to adverse foetal and maternal outcomes. Aims and Objective: The current study aimed to estimate the prevalence of asymptomatic bacteriuria (ABU), its associated risk factors, bacterial isolates and antimicrobial sensitivity pattern in pregnant women attending Outpatient department (services in a tertiary hospital in India. Materials and Methods: This was a hospital-based cross-sectional study among asymptomatic women coming for routine antenatal check-ups to obstetrics OPD of a teaching hospital in Northern India. Samples were collected, processed and antimicrobial sensitivity done as per Clinical and Laboratory Standards Institute (CLSI) guidelines. Data was analysed and p value below 0.05 was considered as statistically significant. Results: Overall 247 pregnant women were included in the study with a mean age of 25.9 ± 3.1. The overall prevalence of asymptomatic bacteriuria was 18.6%. The most common isolates responsible for ABU were E. Coli (48%), S Aureus (23%), K. pneumonia (12%), Pseudomonas (6%), Enterococcus (6%), Proteus (5%). Gram-negative isolates were mostly sensitive to Fosfomycin, Meropenem, Piperacillin + Tazobactum whereas gram-positive isolates were usually sensitive to Fosfomycin, Vancomycin and Linezolid Most isolates were resistant to Co-amoxiclav, Ciprofloxacin, and Nitrofurantoin. Conclusion: Considering the high prevalence of ABU and its association with adverse maternal and foetal outcomes, urine culture should be included in routine investigations being offered to pregnant women. Gram-negative bacteria were the primary causative agents with Fosfomycin, Meropenem and Ceftazidime showing high level of efficacy against the pathogens.